2022
DOI: 10.1002/ajb2.16047
|View full text |Cite
|
Sign up to set email alerts
|

Selection against early flowering in geothermally heated soils is associated with pollen but not prey availability in a carnivorous plant

Abstract: Premise In high‐latitude environments, plastic responses of phenology to increasing spring temperatures allow plants to extend growing seasons while avoiding late frosts. However, evolved plasticity might become maladaptive if climatic conditions change and spring temperatures no longer provide reliable cues for conditions important for fitness. Maladaptative phenological responses might be related to both abiotic factors and mismatches with interacting species. When mismatches arise, we expect selection to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In our study, observed temperature‐dependent selection on flowering time might also have been mediated by interactions with pollinators and herbivores. Although we did not investigate the role of pollinators in this study, a study with Pinguicula vulgaris in the same area showed that fitness decreased with increasing soil temperature in untreated plants but increased with temperature in plants supplemented with pollen (Valdés et al, 2022). This suggests that early‐flowering plants in warm soils might receive fewer pollinator visits, for example, because pollinators experience a different degree of warming, or because the sensitivity to temperature differs between plants and pollinators (Kharouba & Vellend, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…In our study, observed temperature‐dependent selection on flowering time might also have been mediated by interactions with pollinators and herbivores. Although we did not investigate the role of pollinators in this study, a study with Pinguicula vulgaris in the same area showed that fitness decreased with increasing soil temperature in untreated plants but increased with temperature in plants supplemented with pollen (Valdés et al, 2022). This suggests that early‐flowering plants in warm soils might receive fewer pollinator visits, for example, because pollinators experience a different degree of warming, or because the sensitivity to temperature differs between plants and pollinators (Kharouba & Vellend, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…It also permits the detection and measurement of the three distinct modes of selection on individual traits: linear, stabilizing (or optimizing), and disruptive selection. In this issue, many of the investigators used selection analysis to examine or to infer the process of selection on traits such as germination time (Muir et al, 2022), flowering phenology (Johnson et al, 2022, MacTavish and Anderson, 2022, Valdés et al, 2022), flower size and height (Chen and Pannell, 2022), plant size at flowering (MacTavish and Anderson, 2022), specific leaf area and plant height (Waterton et al, 2022), and physiological performance (Mazer et al, 2022; see also Johnson et al, 2022).…”
Section: Manipulative and Observational Studies Of Phenotypic Selectionmentioning
confidence: 99%
“…Valdés et al (2022) investigated whether mean flowering time, mean fitness, and the pattern of selection on flowering time in the carnivorous common butterwort, Pinguicula vulgaris (Lentibulariaceae), are influenced by geothermally heated local soil temperature, experimentally manipulated pollination intensity, and prey availability. In addition, they assessed whether the plastic response of flowering time to environmental conditions was maladaptive based on the environment‐specific patterns of selection on this trait.…”
Section: Manipulative and Observational Studies Of Phenotypic Selectionmentioning
confidence: 99%
See 1 more Smart Citation